Blue Economy dalam Upaya Pengentasan Kemiskinan Masyarakat Pesisir di Indonesia - Apriliana, Tria; Fathonah, Andina Nur; Ali, Muhammad (Ekonomis: Journal of Economics and Business, 2024)
The potential for utilization of the Indonesian maritime sector is very large, but it has not been utilized optimally. In efforts to develop the maritime sector, Indonesia faces the challenge of improving the economy in the maritime sector, but also has to maintain existing sustainability, which is stated in the blue economy concept. This research aims to determine the effect of the number of fishermen and the number of marine capture fishing vessels on poverty through the volume of capture fisheries production and the value of capture fisheries production in Indonesia. This research examines 34 provinces in Indonesia for the 2021 period using path analysis techniques. The results of the research show that the number of fishermen has a significant influence on the volume of capture fisheries production, the number of fishermen has no significant influence on the value of capture fisheries production, the number of capture fisheries vessels has a significant influence on the volume of capture fisheries production, the number of capture fisheries vessels has no significant influence on the value of capture fisheries production, the volume of capture fisheries production has a significant effect on the production value of capture fisheries, the production value of capture fisheries does not have a significant effect on gross regional domestic product, and the production value of capture fisheries does not have a significant effect on environmental quality in Indonesia.